Phytochemical Profiling and Biological Activities of Two Underutilized Wild Leafy Vegetables, Cryptocoryne retrospiralis (Roxb.) Kunth and Glinus oppositifolius (L.) Aug. DC: A GC-MS Analysis - Nakade, Jayendra Giridhar; Nasare, Praveenkumar Narayanrao. (Asian Journal of Biological and Life Sciences, 2026)
Background: Cryptocoryne retrospiralis (Roxb.) and Glinus oppositifolius (L.) Aug. DC. are wild leafy vegetables traditionally utilized in folk medicine for their therapeutic potential. The present study aimed to evaluate their antimicrobial and antioxidant activities, along with profiling their phytochemical constituents. Materials and Methods: Plant samples were collected from their natural habitat in the Gadchiroli district, Maharashtra. Leaf extracts were prepared using solvents of varying polarity, including water, ethyl acetate, methanol, chloroform, and acetone. Antimicrobial activity was assessed using the disc diffusion method against selected microbial strains. Antioxidant potential was determined through the colorimetric DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. Methanolic extracts were further subjected to Gas Chromatography-Mass Spectrometry (GC-MS) analysis, and compounds were identified using the NIST spectral database. Results: The antimicrobial analysis revealed that the chloroform extract of C. retrospiralis exhibited the highest activity, with zones of inhibition measuring 16 mm against Staphylococcus aureus and 12 mm against Pseudomonas fluorescens. Similarly, the methanolic extract of G. oppositifolius demonstrated inhibition zones of 14 mm and 12 mm against S. aureus and P. fluorescens, respectively. Both plant species showed notable antioxidant activity in methanolic extracts as determined by the DPPH assay. GC-MS analysis identified a total of 78 and 86 phytochemical compounds in C. retrospiralis and G. oppositifolius, respectively. Key compounds detected included pyridine derivatives (e.g., Pyridine, 1-acetyl-1,2,3,4-tetrahydro-) and Melezitose, among others with reported biological significance. Conclusion: The findings suggest that C. retrospiralis and G. oppositifolius are rich sources of bioactive phytoconstituents with promising antimicrobial and antioxidant properties, highlighting their potential applications in pharmaceutical and nutraceutical development.
Keywords: Antioxidant; Cryptocoryne retrospiralis; Glinus oppositifolius; Phytoconstituents; Wild; leafy vegetable